Comprehensive Multi-Disciplinary Assessment Protocol for Autism Spectrum Disorder (Journal of Intellectual Disability - Diagnosis and Treatment, 2014)
Legal mandates established under IDEA specify a student must be assessed in all areas of suspected disability. Never is this task more overwhelming than its application to the assessment of a student suspected of a diagnosis of autism. The assessment of an individual suspected of an autism spectrum disorder (ASD) diagnosis is a complex task and is dependent on the integration of information gleaned from assessments conducted by an array of professionals, each with their own distinct area of expertise. The purpose of this article is to introduce the Comprehensive Multidisciplinary Assessment Protocols-Autism Spectrum Disorder, referred to as the CMAPs, as a mechanism for organizing multidisciplinary team assessments. The CMAPs were developed in response to the challenges experienced by school-based assessment teams in developing appropriate and legally defensible assessment plans. The CMAPs provide teams a systematic, organizational, and comprehensive platform to organize the assessment of students across the spectrum of the disorder with the goal of making the task less overwhelming.  Each assessment protocol considers the assessment needs of individuals with ASD using their communication skills as a preliminary starting point.